Tuberculous Dactilitis in Young Male, a Rare Case - Yusdianto, Adrian; Tantular, Rezki; R. Sugiri, Yani Jane; Rahayu Sartono, Teguh; Rachma Erawati, Dini; Setyo Yudhanto, Hendy (Malang Respiratory Journal, 2023)
Introduction : Chylothorax is an uncommon medical condition caused by the accumulation of chylous fluid in the pleural space. Chylothorax has no predilection for sex or age. The prevalence after various cardiothoracic surgeries is 0.2% to 1%. Mortality and morbidity rates are around 10%. Respiratory distress may occur due to compression of the lung by the accumulated fluid. Management and approaches to treating the condition require multidisciplinary therapy, starting from non-pharmacological, pharmacological, to interventional management. Case Report : A 57-year-old Man patient was referred to the emergency room with chief complaint of shortness of breath. Reduced breathing sound on both lung fields. No previous history of cancer or thoracic surgery were found. X-ray examination had found bilateral pleural effusion. Thoracocentesis and pleural fluid analysis was performed with total of 6800 cc serosanguinous, whitish fluid was extracted from both of the lung. The patient was diagnosed with chylothorax. Lymphangiography and embolization was performed on the leak on left thoracic duct (T10) from right lymph node. Antibiotic was also given to treat the community acquired pneumonia that could be one of the possible etiology on this patient. Dietary modification with low fat diet and Ocreotide was also given to this patient as one of the treatment modalities. Discussion : The diagnosis of Chylothorax on this patient was established based on pleural fluid analysis and evidenced by lymphangiography examination by the presence of a leak in the thoracic lymphatic duct. Various modalities to  diagnose this condition have been carried out with inconclusive results. Non-pharmacological, pharmacological and radiological interventions with embolization through lymphangiography are proven to be able to stop leaks and reduce symptoms in this patient. Conclusion : Chyle leak to the pleural space may compress the lung and cause respiratory distress. Combinaton of thoracocentesis, embolization of the leakage, dietary intake modification and administration of ocreotide may help prevent further chylous fluid accumulation.